Influence of social support on subjective well-being of patients with chronic diseases in China: chain-mediating effect of self-efficacy and perceived stress - Luo, Zhenni; Zhong, Sisi; Zheng, Siyu; Li, Yun; Guan, Yan; Xu, Weihong; Li, Lu; Liu, Siyuan; Zhou, Haozheng; Yin, Xuanhao; Wu, Yibo; Liu, Diyue; et al. (Frontiers in Public Health, 2023)
Introduction The well-being of patients with chronic diseases is an issue of widespread concern in public health. While social support is thought to have a positive effect on it, the mechanisms of its influence have not been fully addressed. Thus, we explored the possible mediating effects of self-efficacy and perceived stress to determine the relationship between social support and well-being in these patients. Methods A cross-sectional study was conducted among 4,657 patients with chronic diseases in China. The PROCESS Macro model 6 of SPSS was employed to explore the intermediary role between variables. Results Self-efficacy and perceived stress played a partial intermediary role between social support and subjective well-being, with an effect ratio of 48.25% and 23.61%, respectively. Self-efficacy and perceived stress had a chain intermediary effect (28.14%) between social support and subjective well-being. Discussion This study suggested that improving the self-efficacy of patients with chronic diseases to cope with the changes in social support caused by the disease could reduce stress and enhance subjective well-being.